Analisis Persepsi Harga dan Nilai dalam Mempengaruhi Minat Beli Konsumen di Nooka Coffee House Depok - Faza Amrullah; Rizki Alif Abbia; Tristan Abdi Syahputra (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the influence of price perception on perceived value and its implications for consumer purchase intention at Nooka Coffee House. In the increasingly fierce competition in the cafe industry, price is a crucial factor that not only affects purchasing decisions but also reflects the quality and experience received by consumers. The problem that arises is the difference in consumer perception of the set price level, which has the potential to affect purchase intention and customer loyalty. The results show that price perception has a positive and significant effect on perceived value. In addition, price perception and perceived value simultaneously also have a significant effect on consumer purchase intention. These findings indicate that the better the consumer's perception of the price, the higher the perceived value and the tendency to make a purchase.